Inflammatory Endotypes in COPD. - Barnes,PJ (Allergy, 2019)
Chronic obstructive pulmonary disease (COPD) is a major global health problem that is poorly treated by current therapies as it has proved difficult to treat the underlying inflammation, which is largely corticosteroid-resistant in most patients. Although rare genetic endotypes of COPD have been recognised, despite the clinical heterogeneity of COPD it has proved difficult to identify distinct inflammatory endotypes. Most patients have increased neutrophils and macrophages in sputum, reflecting the increased secretion of neutrophil and monocyte chemotactic mediators in the lungs. However, some patients also have increased eosinophils in sputum and this may be reflected by increased blood eosinophils. Increased blood and sputum eosinophils are associated with more frequent exacerbations and predict a good response to corticosteroids in reducing and treating acute exacerbations. Eosinophilic COPD may represent an overlap with asthma but the mechanism of eosinophilia are uncertain as, although an increase in sputum IL-5 has been detected, anti-IL-5 therapies are not effective in preventing exacerbations. More research is needed to link inflammatory endotypes to clinical manifestations and outcomes in COPD and in particular to predict response to precision medicines. This article is protected by copyright. All rights reserved.